2022
DOI: 10.1111/1911-3846.12794
|View full text |Cite
|
Sign up to set email alerts
|

Walking the Talk? Managing Errors in the Audit Profession*

Abstract: Errors reflect unintended deviations from plans or goals and commonly carry negative connotations. Although errors cannot be eliminated, they offer opportunities for learning and innovation. Audit firms employ powerful mechanisms, such as review processes, to prevent or detect audit errors and safeguard their work in the public interest. At the same time, the profession recognizes positive longterm outcomes of errors in terms of continuous learning to enhance auditor skills and, ultimately, audit quality. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…In their interview study on error management in auditing, Gold et al (2022) reveal that in the wake of significant pressure on the profession, audit firms predominantly focus on error prevention, rather than fully embracing the learning potential of errors to improve their performance. Practitioners describe a series of work conditions that appear to influence error learning, such as the potential consequences of errors for the client, the types of errors dealt with, and experiencing emotions in connection with errors, along with experienced time pressure.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In their interview study on error management in auditing, Gold et al (2022) reveal that in the wake of significant pressure on the profession, audit firms predominantly focus on error prevention, rather than fully embracing the learning potential of errors to improve their performance. Practitioners describe a series of work conditions that appear to influence error learning, such as the potential consequences of errors for the client, the types of errors dealt with, and experiencing emotions in connection with errors, along with experienced time pressure.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…First, auditors, like other professionals, make errors that vary in their consequences (Gold et al, 2022). While all errors, regardless of their consequences, carry learning potential (van Dyck, 2009), prior research has shown that learning is more likely to occur when an error has relatively larger consequences, usually affecting the person committing the error or others, with regard to individuals' health, finances, or social standing (Cannon and Edmondson, 2005;Homsma et al, 2009).…”
Section: Small Error Consequencesmentioning
confidence: 99%
See 3 more Smart Citations